Analisa Produktivitas Crude Palm Oil (CPO) Menggunakan Metode Value Stream Mapping (VSM) (Studi Kasus: PTPN V Sei. Galuh, Kampar, Riau) - Muhammad Sholihin; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The Value Stream Mapping (VSM) is a mapping tool for viewing of process flow and information flow, which can help to differentiate value added and non- value added in production processes. This study aims to analyze the productivity of CPO using the VSM method (case study: CPO processing in PKS PTPN V Sei Galuh). PKS PTPN V Sei. Galuh is engaged in the palm oil processing industry that produces CPO and kernels. The research method used fish bone diagram, VSM and Process Activity Mapping (PAM) diagram to analyze CPO processing productivity. The result of this research revealed time of PAM of 1.4226 seconds/kg, while the standard time of processing company was 1.0292 seconds/kg. That was meant the value of processing productivity of 72.34%, which it needs to eliminate wastes to achieve the company target. The productivity of CPO produced an average of 66.11% for research period. Then,the current VSM was defined processing time total of value added of 1.289 seconds/kg, non-value added of 0.036 seconds/kg and activities of necessary non-value added of 0.1008 seconds/kg. Furthermore, after result of processing of the Future Value Stream Mapping (FVSM) can be eliminated the processing time total became 1.2028 seconds/kg,which value added of 1.102 seconds/kg, non-value added of 0 seconds/kg and necessary non-value added of 0.1008 seconds/kg. Based fish bone diagram analysis can be identified the wastes due to the raw material, working method, human, equipment and work environment. The largest waste contributor was improving raw material quality, because it lead to longer processing time.Keyword : Mapping, Waste Production, Fishbone Diagram